Caspase 3-mediated stimulation of tumor cell repopulation during cancer radiotherapy - Huang, Qian (2011)
In cancer treatment, apoptosis is a well-recognized cell death mechanism through which cytotoxic agents kill tumor cells. Here we report that dying tumor cells use the apoptotic process to generate potent growth-stimulating signals to stimulate the repopulation of tumors undergoing radiotherapy. Surprisingly, activated caspase 3, a key executioner of apoptosis, plays key roles in the growth stimulation. One downstream effector that caspase 3 regulates is prostaglandin E(2), which can potently stimulates growth of surviving tumor cells. Deficiency of caspase 3 either in tumor cells or in tumor stroma caused significant tumor sensitivity to radiotherapy in xenograft or mouse tumors. In human cancer patients, higher levels of activated caspase 3 in tumor tissues are correlated with significantly increased rate of recurrence and deaths. We propose the existence of a “Phoenix Rising” pathway of cell death-induced tumor repopulation in which caspase 3 plays key roles.